Studying of genetic differentiation among clupisoma sinensis, ompok bimaculatus, puntius sophore & labeo rohita species into vishnupuri & jaikwadi dams in godavari river of the system utilizing mtDNA Gene - Rabeeha Mankhi Jebur (Open Journal of Biological Sciences - Peertechz Publications, 2020)
Throughout this research, twenty specimens (Puntius sophore , Clupisoma sinensis, Labeo rohita, and Ompok bimaculatus) in both different locations ( Vishnupuri & Jaikwadi Dams) in Rivers of Godavari were collected in the network. DNA isolation & specific cytochrome b gene amplification primes were planned, followed by DNA Technical quantification of PCR where the cytb gene for (C. sinensis & O. bimaculatus ) was amplified by (1066 bp) in length while the long of (L. rohita and P. sophore) was (1252 bp), For each species, after the cytb gene sequencing phase was completed, then sequences were eventually analyzed on all species. Current study indicated that 14 samples for (Clupisoma sinensis) were explored for nucleotide composition at the Vishnupuri dam while 16 samples for (O. bimaculatus) at Jaikwadi [C (28.5%) , G (14.5%), T (U) (27.7%), A (29.4%)] &[ A (29.0%), G (14.4%), C(30.1%), T(U) (26.5%)], respectively. Diversity of nucleotides, Pi(t) between the Nanded and Paithan populations was 0.09309. One Clupisoma sinensis haplotype was formed while two Ompok bimaculatus haplotypes were established, which refers to a low genetic variability of (O. bimaculatus), where the analysis of UPGMA cluster found sequence differentiation only within (O.bimaculate) but none any variance in (C.sinensis). Unluckily, due to certain technical reasons, the other species (Puntius sophore & Labeo rohita) unacquired their cytb gene sequences, consequently we reached for our aim in the present study to determine the genetic variation among out of 2 species from total 4 species of fishes in two different regions.